Risk of venous thromboembolism in patients with COVID‐19: A systematic review and meta‐analysis. Issue 7 (13th October 2020) - Nopp, Stephan; Moik, Florian; Jilma, Bernd; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: Venous thromboembolism (VTE) is frequently observed in patients with coronavirus disease 2019 (COVID‐19). However, reported VTE rates differ substantially. Objectives: We aimed at evaluating available data and estimating the prevalence of VTE in patients with COVID‐19. Methods: We conducted a systematic literature search (MEDLINE, EMBASE, World Health Organization COVID‐19 database) to identify studies reporting VTE rates in patients with COVID‐19. Studies with suspected high risk of bias were excluded from quantitative synthesis. Pooled outcome rates were obtained within a random effects meta‐analysis. Subgroup analyses were performed for different settings (intensive care unit [ICU] vs non‐ICU hospitalization and screening vs no screening) and the association of d ‐dimer levels and VTE risk was explored. Results: Eighty‐six studies (33, 970 patients) were identified and 66 (28, 173 patients, mean age: 62.6 years, 60.1% men, 19.4% ICU patients) were included in quantitative analysis. The overall VTE prevalence estimate was 14.1% (95% confidence interval [CI], 11.6‐16.9), 40.3% (95% CI, 27.0‐54.3) with ultrasound screening and 9.5% (95% CI, 7.5‐11.7) without screening. Subgroup analysis revealed high heterogeneity, with a VTE prevalence of 7.9% (95% CI, 5.1‐11.2) in non‐ICU and 22.7% (95% CI, 18.1‐27.6) in ICU patients. Prevalence of pulmonary embolism (PE) in non‐ICU and ICU patients was 3.5% (95% CI, 2.2‐5.1) and 13.7% (95% CI, 10.0‐17.9). Patients developing VTE had higher d ‐dimer levels (weighted mean difference, 3.26 µg/mL; 95% CI, 2.76‐3.77) than non‐VTE patients. Conclusion: VTE occurs in 22.7% of patients with COVID‐19 in the ICU, but VTE risk is also increased in non‐ICU hospitalized patients. Patients developing VTE had higher d ‐dimer levels. Studies evaluating thromboprophylaxis strategies in patients with COVID‐19 are needed to improve prevention of VTE.